VARIATION OF GASTROCNEMIUS FLAP AND THEIR APPLICATIONS - Abas, Muhammad Firdaus (International Journal of Allied Health Sciences, 2021)
In Hospital Tengku Ampuan Afzan, Kuantan a total of 145 cases referred for lower limb reconstruction in 4 years duration and 22 cases the option of reconstruction is gastrocnemius flap. Gastrocnemius Flap is useful flap in lower limb reconstruction. It is reliable, relatively easy to raise and can be used by non-specialized reconstructive surgeon. The flap main application is for the upper part of the leg and knee region. The flap variations include either the use of medial or lateral head. Its component variations include muscle, musculocutaneous and inclusion of part of the tendon. All have its own advantages and useful in complex defect of the upper part of the leg and knee region. Complex wound, exposed implant, revision surgery and infected wound are among the indications for the usage of gastrocnemius flap. In conclusion gastrocnemius flap is the armamentarium flap in lower limb reconstruction. Its provide well vascularized coverage and with musculocutaneous variations it can be raised as large flap and avoid more complex reconstructive procedure.